Avaliação do desempenho acústico de um escritório de planta livre construído com madeira engenheirada - Andrade, Fernanda Horst (2025)
This study presents an analysis of the acoustic performance of an open-plan office environment, with emphasis on the use of recycled wood panels made of Medium Density Particleboard (MDP) in internal partition systems. The research was conducted on two main fronts: the evaluation of acoustic conditioning within the workspace and the assessment of sound insulation between meeting rooms, in accordance with the guidelines of standards ABNT NBR ISO 3382-3:2022, ABNT NBR ISO 16283-1:2018, and ISO 717-1:2020. In the open-plan space, parameters such as the A-weighted sound pressure level at 4 m from the source Lp,A,S,4m, comfort distance rc, spatial decay of speech D2,S, and Speech Transmission Index STI were analyzed through in situ measurements. The results for Lp,A,S,4m were 39,10 dB and 38,01 dB, with corresponding comfort distances of 1,13 m and 1,01 m for the two workstation configurations analyzed, both complying with normative limits. The distraction distance rD, derived from the spatial distribution of STI, was found to be 7,45 m and 6,82 m, indicating the environment’s effectiveness in reducing speech intelligibility over greater distances. Regarding sound insulation between meeting rooms, both experimental tests and simulations using the INSUL software were carried out to evaluate the performance of an Internal Vertical Partition System composed of MDP panels. The simulation yielded a Weighted Sound Reduction Index Rw of 38 dB, a result comparable to that obtained for a similar system using gypsum boards, highlighting MDP’s technical potential as a sustainable alternative. Field measurements indicated a Weighted Apparent Sound Reduction Index R′w of 31 dB, with spectral adaptation terms C equal to –2 and Ctr equal to –3, reflecting the influence of flanking transmissions on overall performance. Nevertheless, the measured Speech Privacy Index SPI was 71 dB, meeting the minimum criterion established by ASTM E2638:2017 for spaces requiring confidentiality. The findings of this study reinforce the viability of recycled wood as a component of acoustically efficient building solutions, providing valuable insights for the development of sustainable and technically sound architectural projects.